Health Information Sources and the Influenza Vaccination: The Mediating Roles of Perceived Vaccine Efficacy and Safety. Issue 9 (1st September 2020) - Hwang, Juwon
Abstract : Although the influenza vaccine is widely recognized as an effective preventive measure, influenza vaccination rates among U.S. adults remain low. Moreover, influenza-related respiratory illnesses may increase the risk of adverse outcomes of COVID-19. Thus, this study examines the mechanisms involved in influenza vaccination uptake. Specifically, this study investigates how health information sources are associated with perceived vaccine efficacy and safety, which, in turn, associated with influenza vaccine uptake. Analyzing cross-sectional survey data from a national U.S. adult sample ( N = 19, 420), mediation analyses were conducted. Results revealed that considering vaccine efficacy, health information seekers who assigned more value to medical professionals, medical journals, and newspaper articles were more likely to perceive a vaccine as effective, thus being more likely to receive the influenza vaccine. By contrast, individuals who placed more value in social media were less likely to perceive vaccine efficacy, and, in turn, were less likely to get the influenza vaccine. Turning to vaccine safety, the value ascribed to medical professionals was positively associated with vaccine safety, which, in turn, related to influenza vaccine uptake. By contrast, social media, family or friends, and promotions were negatively associated with vaccine safety, and then influenza vaccine uptake.